A Case of Traumatic Pancreaticoduodenal Injury: A Simple and an Organ-Preserving Approach as Damage Control Surgery - Choi, Sae Byeol; You, Jiyoung; Choi, Sang Yong (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "맑은 고딕"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "맑은 고딕"; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA;" lang="EN-US"> Traumatic pancreaticoduodenal injury still remains challenging with high morbidity and mortality. Optimal management by performing simple and fast damage control surgery ensures better outcomes. Case report A 36-year-old man was admitted with a combined pancreaticoduodenal injury after being assaulted. More than 80% of duodenal circumference (first portion) was disrupted and the neck of the pancreas was transected. Primary repair of the duodenum and pancreaticogastrostomy were performed. The stump of the proximal pancreatic duct was also sutured. The patient developed an intra-abdominal abscess with pancreatic fistula that eventually recovered by conservative treatment. Conclusion Pancreaticogastrostomy can be a treatment option for pancreatic transection. Rapid and simple damage control surgery with functional preservation of the organ will be beneficial for trauma patients.